Feeding barrows and gilts three protein sequences to heavier market weight - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Forty-eight Yorkshire barrows and 48 Yorkshire gilts were fed separately three protein sequences to a finish weight of 250 to 260 lbs. Barrows gained faster and were more efficient on protein sequence B (16% protein diet from 100 to 135 lbs.; then 14% diet to finish weight) and C (same as B except that barrows were switched at 210 lbs. to a 12% diet to final weight) than on A (16% protein diet from 100 lbs. to final weight). Gilts gained fastest and were most efficient when fed sequence A. Both barrows and gilts gained slower after attaining the weight of 215 lbs., ate less feed per day, and required more than 4 lbs. of feed per pound of gain from 215 to 250+ lbs. Carcasses of barrows, regardless of protein sequences, were similar in backfat, loin eye, and length.
Bright Future? is known as Swine Day, 1977
Keywords: Swine; Barrows; Gilts; Protein; Heavy market weight